Enhancing mechanical properties and wear resistance of dual phase steel through surface mechanical attrition treatment - Lokendra Kumar Katiyar (Results in Surfaces and Interfaces)
The study investigates the mechanical properties of dual-phase (DP) steel undergoing surface martensite transformation through Surface Mechanical Attrition Treatment, revealing phase transformation and grain refinement, increasing exponentially with treatment duration. After 40 min of SMAT, X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) analyses revealed approximately 37% martensite and 63% ferrite phases, in contrast to 5% martensite and 95% ferrite phases in the as-received state. The surface hardness of the steel increased to 270 VH0.05 (up from 145 VH0.05), while the yield strength rose to 405 MPa (up from 258 MPa). Furthermore, a 60% reduction in the specific wear rate of the steel was achieved. This study highlights SMAT as an innovative method for tailoring the microstructure of steel and enhancing its mechanical properties through stress-induced phase transformation.